Effect of Protease in Commercialized Detergent Powder on Blood Removal Efficiency - LEE, TE CHUAN; Xin Tian, Lee; SELIMIN, MOHAMAD ALI (Research in Management of Technology and Business, 2022)
Blood is one of the most dangerous things to clean up because most diseases spread through blood. The problem that motivates this research is that commercial detergents on the market today are difficult to completely remove the bloodstain on the cloth. The goals of this study are to determine the efficacy of blood removal detergent powder under various raw material compositions and temperatures. To test the effectiveness of removing blood stains, two brands of commercialised detergent powder were used. The protease concentration in the detergent powder was varied from 0% to 10% in this experiment. The washing temperatures were set to 27 °C, 40 °C, 60 °C, and 80 °C. The detergent powder’s effectiveness was tested using chicken blood. The results show that commercialised detergent powder X with a 10% protease addition and a washing temperature of 27 °C were the best conditions.